Laser diode array (LDA) end-pumped multi-watt Yb:YAG 1030 nm laser - Cao, Hongzhong; Peng, Hongyan; Zhang, Meiheng; Chen, Yuqiang; Zhang, Bing; Chen, Baoling; Zhang, Jun; Wu, Tonghua; Zhao, Xiangmin; Tan, Huiming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A LDA (laser diode array) end-pumped Yb:YAG 1030 nm laser is reported. Using a plano-concave resonator, with input pump power of 11.79 W, 2.55 W TEM00 continuous wave laser at 1030 nm was obtained. The effective focal length of the thermal lens is also calculated.
Optica Applicata, Vol. 40, 2010, nr 3, s. 653-656
Keywords: optyka; all-solid-state laser; Yb:YAG; 1030 nm